Programs to improve adolescent sexual and reproductive health in the US: a review of the evidence - Manlove, Jennifer (Adolesc Health Med Ther, 2015)
BACKGROUND: US adolescents have high rates of teen pregnancy, childbearing, and sexually transmitted infections (STIs), highlighting the need to identify and implement effective programs that will help improve teen sexual and reproductive health. MATERIALS AND METHODS: This review identified 103 random-assignment evaluations of 85 programs that incorporated intent-to-treat analyses and assessed impacts on pregnancy, childbearing, STIs, and their key determinants – sexual activity, number of sexual partners, condom use, and other contraceptive use – among teens. This review describes the evidence base for five broad program approaches, including abstinence education, comprehensive sex education, clinic-based programs, youth development programs, and parent–youth relationship programs. We also describe programs with impacts on key outcomes, including pregnancy/childbearing, STIs, and those that found impacts on both sexual activity and contraceptive use. RESULTS: Our review identified 52 effective programs: 38 with consistent impacts on reproductive health outcomes, and 14 with mixed findings (across subpopulations, follow-ups, or multiple measures of a single outcome). We found that a variety of program approaches produced impacts on sexual and reproductive health outcomes. Parent–youth relationship programs and clinic-based program evaluations more frequently showed impacts than other program approaches, although we also identified a number of abstinence-education, comprehensive sex education, and youth-development programs with impacts on sexual and reproductive health outcomes. Overall, we identified nine program evaluations with impacts on teen pregnancies or births, five with impacts on reducing STIs, and 15 with impacts on both delaying/reducing sexual activity and increasing contraceptive use (including condom use). CONCLUSION: Future efforts should conduct replications of existing program evaluations, identify implementation components linked to impacts, rigorously evaluate programs that appear promising, and expand the evidence base on programs that impact hormonal and long-acting contraceptive method use.